Identification of Staphylococcus and Micrococcus species with the STAPHYtest system - Sedlácek, I; Kocur, M (Folia microbiologica, 1991)
A collection of 216 well-characterized strains of Staphylococcus, Micrococcus and Stomatococcus was examined by a commercially available STAPHYtest system (Lachema, Brno, Czechoslovakia). The results of STAPHYtest agreed with those of conventional tests. The STAPHYtest permitted a clear-cut separation of Staphylococcus from Micrococcus and Stomatococcus strains and correctly identified 104 of 145 (72%) Staphylococcus strains after 24 h of incubation. However, it allowed the identification only of 19 of 29 validly published Staphylococcus species. The STAPHYtest proved to be a simple and rapid system for the separation of staphylococci from micrococci and for the identification of most frequent clinically significant staphylococci.
Keywords: bakteriologické techniky; Bacteriological Techniques; Evaluation Studies as Topic; Staphylococcus; hodnotící studie jako téma; Micrococcus